Representasi Tokoh Pewayangan Purwa Pandawa Gagrag Surakarta - Penina Inten Maharani; Birmanti Setia Utami; Jasson Prestiliano (Universitas Negeri Medan, 2019)
The trend of initiating art design carrying wayang as the theme, is an attempt initiated by young generation that is worth-appreciated. However, the process of at design-making itself mostly does not genuinely pay attention to the essentials that each wayang figure has. Omitting or replacing one of the elements of Wayang Purwa could possibly change the values of wayang itself. This study is conducted to arrange a representative figure of Wayang Purwa, which is, Pandawa gagrak Surakarta as the principle of the design making without excluding the meanings and identities of the character. The method used in this study is qualitative, obtained from various references, such as; books, articles, and journals related to the Pandawa gagrak Surakarta figure, and interview with Bambang Suwarno, as a puppeteer as well as a leather wayang crafter. The result of this research is a reference of the Pandawa Lima and Gatotkaca figures design, as mostly used in various media.